Peningkatan Kesadaran Keamanan Data dan Jaringan Melalui Webinar dan Workshop - Luqman Ali Dinul Ramadhan; Agung Firmansyah; Muhammad Kamal Ibrahim; Muhammad Bilal Taqwa; Muhammad Azril Naufal Shadiq; Muhammad Jihan Maulana Zuhri; Popy Meilina; Rita Dewi Risanty; Yana Adharani; Sitti Nurbaya Ambo; Hendra; Rully Mujiastuti (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Public Wi-Fi users in Indonesia remain largely unaware of how easily unencrypted traffic exposes their login credentials, a gap that has enabled data theft and fraudulent online loan applications filed under stolen identities. This community service activity, part of the KKN Diseminasi Magang dan Studi Independen Bersertifikat Batch 10 program, aimed to raise data and network security awareness among students and teachers from three partner schools, SMA Dewan Dakwah Bekasi, MTsN 24 Jakarta Timur, and SMK Perguruan Cikini Jakarta, along with the general public. The team carried out four stages: a needs analysis of the partner schools, preparation of teaching materials and event administration, a one-day online webinar and workshop held via Zoom on 27 June 2026, and an evaluation using pre-test, post-test, and feedback instruments. Of 98 registrants, 53 participants completed the full session. Material covered network threats, the HTTP/HTTPS distinction, encryption and hashing, public-network attack techniques, a Wireshark-based sniffing demonstration, Have I Been Pwned checks, and two-step verification. Average scores rose from 82.68 before the session to 93.45 afterward, a gain of 10.77 points, while feedback showed most participants rated the material's relevance and delivery highly. These results indicate that pairing conceptual explanation with hands-on demonstration measurably improved participants' understanding of public network security risks.